Post translational modifications in tuberculosis: ubiquitination paradox. Issue 3 (4th March 2021) - Shariq, Mohd; Quadir, Neha; Sheikh, Javaid Ahmad; Singh, Alok Kumar; Bishai, William R.; Ehtesham, Nasreen Z.; Hasnain, Seyed E.
ABSTRACT: Innate immune signaling and xenophagy are crucial innate defense strategies exploited by the host to counteract intracellular pathogens with ubiquitination as a critical regulator of these processes. These pathogens, including Mycobacterium tuberculosis ( M. tb ), co-opt the host ubiquitin machinery by utilizing secreted or cell surface effectors to dampen innate host defenses. Inversely, the host utilizes ubiquitin ligase-mediated ubiquitination of intracellular pathogens and recruits autophagy receptors to induce xenophagy. In the current article, we discuss the co-option of the ubiquitin pathway by the M. tb virulence effectors. Abbreviations : ANAPC2: anaphase promoting complex subunit 2; IL: interleukin; Lys: lysine (K); MAPK: mitogen-activated protein kinase; MAP3K7/TAK1; mitogen-activated protein kinase kinase kinase 7; M. tb: Mycobacterium tuberculosis ; NFKB/NF-κB: nuclear factor kappa B subunit; PtpA: protein tyrosine phosphatase; SQSTM1/p62: sequestosome 1; V-ATPase: vacuolar-type H+-ATPase; UBA: a eukaryotic-like ubiquitin-associated domain